Podejścia upełnomocniające w pracy socjalnej - Ciczkowska-Giedziun, Małgorzata (Pedagogika Społeczna Nova, 2023)
This paper explores the issues of current achievements in the field of the empowering approaches in social work. The analyses are complemented by drawing attention to the limitations resulting from their application in practice. The genesis of thinking about empowerment in social work can be found in the works of its precursor Helena Radlińska, particularly in the theory of social strengths. Other inspirations for empowering approaches to social work come from constructivist, as well as from the models based on strengths, such as the constructive social work of Nigel Parton and Patrick O’Byrne, the strengths-based social work of Charles Rapp, Dennis Saleebey and Patrick Sullivan, the solution-focused approach of Steve de Shazer, Insoo Kim Berg, and strengths-based work models (FGC, VIT). Less popular in social work is to refer to systemic (operational) constructivism of Niklas Luhmann’s. The analysis undertaken in the article aims to show these approaches, as well as the changes that are taking place in thinking about social work.